The effect of mind mapping on young children's critical thinking skills - POLAT, ÖZGÜL (ELSEVIER SCI LTD, 2020)
Educational practices are highly significant for the development of critical thinking. Mind mapping is one of the practices which supports the skills of individuals such as interpretation, analysis, explanation and evaluation. This study aims to analyse the effect of mind mapping studies which support critical thinking skills through philosophical inquiry, on such skills of the children aged 48-72 months. Research was conducted with 116 children who receive education in six classes within a preschool educational institution located in Istanbul. The research consisted of experimental group-1 which was subjected to individual mind mapping studies, experimental group-2 which were included in large group mind mapping studies and the control group which continued with the current Preschool Curriculum of the Ministry of Education. The practices completed within eight weeks. In line with the results of the analyses, it was understood that the critical thinking skills scores of children in the experimental group-1 and experimental group-2 were significantly higher than the children in the control group. It was also found that experimental group-2 who large group performed mind mapping made progress further than those of the children in experimental group-1 subjected to individual mind mapping studies.
Keywords: Critical thinking skills; Mind mapping; Preschoolers; Philosophical inquiry; PHILOSOPHY; DISPOSITIONS